From foundation to profession: engaging prospective pharmacy students at UiTM Dengkil - Zulkifli, Nur Wahida; Mohd Tazizi, Mohammad Hafizie Dianel; Mohd Nasir, Ahmad Merza; Ariffin, Nur Syamimi; Jahidin, Aisyah Hasyila (Faculty of Pharmacy, 2026)
The Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), participated in the UiTM Festival Perform held on 7 February 2026 to promote the Bachelor of Pharmacy (Undergraduate) programme to foundation (Asasi) students at UiTM Dengkil. This initiative aimed to increase awareness, provide accurate information, and encourage prospective students to consider pharmacy as a future career pathway.